2014
DOI: 10.1021/am5024435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TiO2 Interfacial Atomic Layers on Device Performances and Exciton Dynamics in ZnO Nanorod Polymer Solar Cells

Abstract: The performances of organic electronic and/or photonic devices rely heavily on the nature of the inorganic/organic interface. Control over such hybrid interface properties has been an important issue for optimizing the performances of polymer solar cells bearing metal-oxide conducting channels. In this work, we studied the effects of an interfacial atomic layer in an inverted polymer solar cell based on a ZnO nanorod array on the device performance as well as the dynamics of the photoexcited carriers. We adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 81 publications
(106 reference statements)
1
23
0
1
Order By: Relevance
“…Various development approaches for efficient materials and well-designed device structures have been investigated to achieve enhanced power conversion efficiency (PCE) of HPV devices [5,6]. Among the developed nanomaterials, ZnO nanorod arrays, which can be grown vertically from a substrate, have great potential for HPV applications because of their ease of synthesis [7,8] and high electron mobilities (*10 2 cm 2 V -1 s -1 ) [9] with a direct transport pathway to the electrode [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various development approaches for efficient materials and well-designed device structures have been investigated to achieve enhanced power conversion efficiency (PCE) of HPV devices [5,6]. Among the developed nanomaterials, ZnO nanorod arrays, which can be grown vertically from a substrate, have great potential for HPV applications because of their ease of synthesis [7,8] and high electron mobilities (*10 2 cm 2 V -1 s -1 ) [9] with a direct transport pathway to the electrode [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the problematic limitation, the concept of bulk heterojunction (BHJ), which has been extensively utilized in organic photovoltaic (OPV) devices [23][24][25], can be performed in the hybrid ZnO/P3HT system. In the concepts of BHJ, donor/acceptor blend films with selfassembled phase separation are able to provide shorter distance for mobile excitons to the interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO is a wide band gap semiconductor with an energy gap of 3.3 eV and a conduction band edge of 4.3 eV. This band edge is sufficiently high to extract electrons from typical donor and acceptor molecules and/or polymers [10]. There are many methods used for the ZnO deposition like spin coating, atomic layer deposition, screen printing, nano-imprinting, pulsed laser deposition, spin-cast and spray coating etc [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This band edge is sufficiently high to extract electrons from typical donor and acceptor molecules and/or polymers [10]. There are many methods used for the ZnO deposition like spin coating, atomic layer deposition, screen printing, nano-imprinting, pulsed laser deposition, spin-cast and spray coating etc [10][11][12][13][14]. Diego Barrera et al reported thermal annealing of P 3 HT:PCBM bulk heterojunctions (BHJs) on top of a commonly used sol-gel ZnO electron transport layer leading to the formation of PCBM clusters [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have exploited thin layers of self-assembled organic dyes or small molecules [25][26][27][28][29][30][31][32][33] to improve the affinity between the oxide surface and the organic active layer. Employing ZnO-TiO 2 core-shell nanorods has been another alternative to improve ZnO interfacial properties since TiO 2 provides higher chemical stability and passivation of surface defects [34][35][36][37][38][39][40]. Several studies have shown improved photovoltaic performances by applying various methods of TiO 2 coatings on ZnO nanorods [34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%